Report on „microGrants ESK 2016” Edition 2016 - Dolińska, Kamilla; Kajta, Justyna; Niedźwiecka-Iwańczak, Natalia (Instytut Socjologii Uniwersytet Wrocławski)
The report on „microGrants ESK 2016” gives the answer to the question of what goals were fulfilled by this programme in the areas of fostering the access to culture and developing the participation in culture (which also includes creating culture) during the year of European Capital of Culture Wrocław 2016. A variety of research methods and tools implemented in the research allowed to collect data from different actors who took part in „microGrants” (i.e. Authors of projects, producers of events, reviewers, audiences, the managing team). Research material was used to present the social perception of the programme which is a key element of the context for the discussion on its sustainability and further development.
Keywords: European Capital of Culture; Wrocław; Programme “microGrants ESK 2016”; culture